2007
DOI: 10.1007/s00256-007-0308-4
|View full text |Cite
|
Sign up to set email alerts
|

Magnetic resonance imaging of bone marrow in oncology, Part 2

Abstract: Magnetic resonance imaging plays an integral role in the detection and characterization of marrow lesions, planning for biopsy or surgery, and post-treatment followup. To evaluate findings in bone marrow on MR imaging, it is essential to understand the normal composition and distribution of bone marrow and the changes in marrow that occur with age, as well as the basis for the MR signals from marrow and the factors that affect those signals; these points have been reviewed and illustrated in part 1 of this two… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
80
1
4

Year Published

2013
2013
2018
2018

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 85 publications
(88 citation statements)
references
References 58 publications
3
80
1
4
Order By: Relevance
“…Otake et al found markedly decreased contrast enhancement of bone marrow both inside and outside the radiation portal (Hwang and Panicek 2007 ;Otake et al 2002 ). Interpretation of these fi ndings differs, the most attractive explanation being fatty conversion due to scatter irradiation (Otake et al 2002 ;Blomlie et al 1995 ).…”
Section: Radiation-induced Changes On Normal Bone Marrowmentioning
confidence: 80%
See 2 more Smart Citations
“…Otake et al found markedly decreased contrast enhancement of bone marrow both inside and outside the radiation portal (Hwang and Panicek 2007 ;Otake et al 2002 ). Interpretation of these fi ndings differs, the most attractive explanation being fatty conversion due to scatter irradiation (Otake et al 2002 ;Blomlie et al 1995 ).…”
Section: Radiation-induced Changes On Normal Bone Marrowmentioning
confidence: 80%
“…The composition B.Jobke and H.Bloem gradually changes from birth to adulthood with the conversion from red to yellow marrow and reaches a static stage between 25 and 30 years of age. The speed of conversion is gender dependent, faster in males than in females (Hwang and Panicek 2007a ;Shapiro 2006 ). Bone marrow fatty conversion progressively starts distally in the extremities and migrates proximally within the extremities towards the axial skeleton in terms of the whole body and from the diaphysis to the metaphysis on the level of the long bones.…”
Section: Bone Marrow Conversion and Reconversionmentioning
confidence: 99%
See 1 more Smart Citation
“…Although rare, malignant lesions such as lymphoma can mimic the signs and symptoms of, or arise from infection, and should be considered in differential diagnoses (7). Because she had no underlying malignancy, it was unlikely that the lesion would prove metastatic, but metastasis may also appear as rim-enhancing lesion (9).…”
Section: Index Termsmentioning
confidence: 99%
“…It is known that treatment induces edema, return of marrow fat, sclerosis or fibrosis [22], resulting in MR signal changes of the bone marrow which are time-and dose-dependent [23]. While T1w reflects marrow replacement and is rather independent of associated sclerosis, STIR reflects more the lesion composition (water content, fibrosis and sclerosis) and shows variable signal [24,25].…”
mentioning
confidence: 99%